Psychological adaptation and posttraumatic stress disorder among Syrian refugees in Germany: a mixed-methods study investigating environmental factors - Anna von Haumeder; Bita Ghafoori; Jeremy Retailleau (European Journal of Psychotraumatology, 2019)
Background: Considering the exposure to potentially traumatic events among the growing refugee population worldwide, there is an urgent need to better understand potential risk and protective factors that may be associated with psychological adaptation in Syrian refugees residing in Germany Objective: The present study examined trauma-related coping self-efficacy, resilience, and environmental factors as predictors of psychological adaptation and posttraumatic stress disorder (PTSD). Method: The present study used a mixed-methods convergent parallel design examining 127 quantitative self-report questionaires and ten qualitative semi-structured interviews.. Results: Quantitative findings showed that nearly half the sample (N = 127) met criteria for probable PTSD (n = 59, 46.5%). Logistic regression models found that lower trauma-related coping self-efficacy (CSE) was independently associated with probable PTSD in unadjusted models (OR = 0.92, 95% CI, 0.88, 0.96, p < .001) and adjusted models (OR = 0.87, 95% CI, 0.82, 0.93, p < .001). Specific environmental factors were significantly inversely related with probable PTSD. Qualitative findings indicated five main themes that were associated with psychological adaptation: 1) language, 2) socioeconomic living conditions, 3) family, 4) discrimination, and 5) asylum procedures. Conclusion: This study suggests that higher perceived ability to deal with the consequences of having experienced potentially traumatic events as well as access to certain environmental factors were associated with better perceived psychological adaptation to German society and better mental health.